The Effect of the Quality of Shopee's Cash on Delivery (COD) Service on Net Benefits with User Satisfaction as an Intervening Variable (A Case Study of Shopee E-Commerce Sellers) - Jannah, Nur Aini Raudhatul; Lutfi Harris (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This study aims to analyze and explain 1) the effect of cash on delivery (COD) service quality on user satisfaction, (2) the effect of user satisfaction on net benefits, (3) the effect of COD service quality on net benefits, and (4) the effect of “COD cek dulu” service quality on net benefits with user satisfaction as an intervening variable. The study employs a quantitative explanatory approach, using a purposively selected sample of 115 respondents and data collected via a survey distributed via Google Forms. The data are analyzed using the Structural Equation Model (SEM) in SmartPLS 4.1. The results exhibit that (1) COD service quality affects user satisfaction, (2) user satisfaction affects net benefits, (3) COD service quality does not affect net benefits, and (4) “COD cek dulu” service quality affects net benefits with user satisfaction as an intervening variable.